1989
DOI: 10.1177/009164718901700202
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Efforts in Cognitive Therapy with Religious Clients

Abstract: therapy requires an under• of and tolerance for the reli• views of clients. Collaborative llniiOL!es in cognitive therapy are de• ond ideological obstacles in cognitive therapy with religious are considered. It is suggested confronting clients' religious beliefs curiOIOC!IICC:n or absolutistic is dini• inappropriate. Beck's and collaborative techniques sed as important clinical in working with religious utcome studies of the usefulness of cognitive therapy have proliferated in recent years, reflecting the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…More delineated findings have been presented in the area of Christian or religious-based psychotherapies due to a rise in the adaptation of religious beliefs into established methodologies such as cognitive-behavioral therapy (CBT). Despite some criticism or limitations of the use of CBT with religious clients (see McMinn, 1991;Tan, 1987), CBT has been shown to be a very useful model with Christian clients (see Craigie, 1992;Lipsker & Oordt, 1990;McMinn & Lebold, 1989), even when delivered by nonreligious therapists (Probst et al, 1992). According to Tan, some common characteristics of Christian therapies that have been developed within the CBT framework include: (a) reliance on Scripture as the primary truth (and not on self-evident truths as in traditional CBT); (b) challenging some of the core assumptions and goals of CBT that emphasize the need for self-efficacy through self-fulfillment (not wholeness through God); and (c) explicitly acknowledging the importance of other factors (historical, social, theological, and familial) that are important in a Christian context.…”
mentioning
confidence: 99%
“…More delineated findings have been presented in the area of Christian or religious-based psychotherapies due to a rise in the adaptation of religious beliefs into established methodologies such as cognitive-behavioral therapy (CBT). Despite some criticism or limitations of the use of CBT with religious clients (see McMinn, 1991;Tan, 1987), CBT has been shown to be a very useful model with Christian clients (see Craigie, 1992;Lipsker & Oordt, 1990;McMinn & Lebold, 1989), even when delivered by nonreligious therapists (Probst et al, 1992). According to Tan, some common characteristics of Christian therapies that have been developed within the CBT framework include: (a) reliance on Scripture as the primary truth (and not on self-evident truths as in traditional CBT); (b) challenging some of the core assumptions and goals of CBT that emphasize the need for self-efficacy through self-fulfillment (not wholeness through God); and (c) explicitly acknowledging the importance of other factors (historical, social, theological, and familial) that are important in a Christian context.…”
mentioning
confidence: 99%
“…The incompatibilities of rational-emotive philosophy and Christianity have recently received considerable attention (Jones, 1989;McMinn & Lebold, 1989;Watson, Morris, & Hood, 1988). McMinn and Lebold (1989) noted that Ellis' assumption that devout religious philosophies need to be altered is not consistent with a Christian therapeutic approach.…”
Section: Religious Critiques Of Rational-emotive Theorymentioning
confidence: 99%
“…McMinn and Lebold (1989) noted that Ellis' assumption that devout religious philosophies need to be altered is not consistent with a Christian therapeutic approach. Watson et al (1988) concluded that Christianity and REP operate as differrent and often competing ideologies and hypothesized that reason alone is not a totally reliable guide to right belief and action.…”
Section: Religious Critiques Of Rational-emotive Theorymentioning
confidence: 99%
See 2 more Smart Citations